Arsenic, cadmium, and lead exposition: a risk factor for breast and prostate cancers? – Protocol for a systematic review (Research, Society and Development, 2023)
Objective: This study aims to develop a protocol for a systematic review of the literature published until April/2021 related to exposure to heavy metals and the development of breast and prostate cancer, to understand the relationship between metals such as arsenic, cadmium, and lead and these types of cancer, considering the characteristics of bioaccumulation of these elements and the intensification of their use in contemporary society. Methodology: The mnemonic PECOS (Population, Exposure, Control, Outcome, and Study Design) will guide the search strategy that will be carried out in eight databases (Pubmed, Pubmed PMC, BVS, Embase, Scopus, Web of Science, Cochrane, and ProQuest). The selection process and data extraction will be conducted by two authors independently. Articles that meet the pre-established inclusion criteria (age over 18 years, exposed metals, type of cancer, case-control, and cohort studies) will be included in the review and, after reading the complete text, will have the data and characteristics extracted and organized in a table containing the bibliometric data and characteristics of the studies (population, data obtained, conclusions and results). Results: They will be presented in a descriptive synthesis followed by tables and diagrams.